Very late vasomotor responses and gene expression with bioresorbable scaffolds and metallic drug‐eluting stents. Issue 4 (24th June 2021) - Koh, Jin‐Sin; Gogas, Bill D.; Kumar, Sandeep; Benham, James J.; Sur, Sanjoli; Spilias, Nikolaos; Kumar, Arnav; Giddens, Don P.; Rapoza, Richard; Kereiakes, Dean J.; Stone, Gregg; Jo, Hanjoong; et al.
Abstract: Objectives: To investigate the long‐term vasomotor response and inflammatory changes in Absorb bioresorbable vascular scaffold (BVS) and metallic drug‐eluting stent (DES) implanted artery. Background: Clinical evidence has demonstrated that compared to DES, BVS is associated with higher rates of target lesion failure. However, it is not known whether the higher event rates observed with BVS are related to endothelial dysfunction or inflammation associated with polymer degradation. Methods: Ten Absorb BVS and six Xience V DES were randomly implanted in the main coronaries of six nonatherosclerotic swine. At 4‐years, vasomotor response was evaluated in vivo by quantitative coronary angiography response to intracoronary infusion of Ach and ex vivo by the biomechanical response to prostaglandin F2‐α (PGF2‐α), substance P and bradykinin and gene expression analysis. Results: Absorb BVS implanted arteries showed significantly restored vasoconstrictive responses after Ach compared to in‐stent Xience V. The contractility of Absorb BVS treated segments induced by PGF2‐α was significantly greater compared to Xience V treated segments and endothelial‐dependent vasorelaxation was greater with Absorb BVS compared to Xience V. Gene expression analyses indicated the pro‐inflammatory lymphotoxin‐beta receptor (LTβR) signaling pathway was significantly upregulated in arteries treated with a metallic stent compared to Absorb BVS treated arterial segments. Conclusions: At 4 years, arteries treated with Absorb BVS compared with Xience V, demonstrate significantly greater restoration of vasomotor responses. Genetic analysis suggests mechanobiologic reparation of Absorb BVS treated arteries at 4 years as opposed to Xience V treated vessels.